In vivo evaluation of anticryptosporidiosis activity of the methanolic extract of the plant Umbilicus rupestris - AFAF BENHOUDA; DJAHIDA BENHOUDA; MASSINISSA YAHIA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Benhouda A, Benhouda D, Yahia M. 2019. In vivo evaluation of anticryptosporidiosis activity of the methanolic extract of the plant Umbilicus rupestris. Biodiversitas 20: 3478-3483. Umbilicus rupestris (Crassulaceae) is a medicinal plant used in general traditional medicine to cure inflammation and irritation of the skin. The present research is aimed to evaluate the antiparasitic activity of the methanolic extract of the plant URMeOH of U. rupestris against the Cryptosporidium infection in immunocompetent and immunosuppressed rats experimentally infected. Twenty-one female rats were divided into two groups. Control group (group I) and experimental group (Group II). The group I was further divided into three equal groups (normal group infected and immunosuppressed infected group). The experimental group was divided into two immunosuppressed and four equal groups and two immunocompetent infected. Cryptosporidium oocysts were isolated from bovine species stools and used to infect rats. Experimental subgroups received URMeOH two as dose 100mg/kg b.w. and 200 mg/kg b.w. and continued until 15 days. Two weeks after the administration of URMeOH, feces of rats were examined for the detection of Cryptosporidium oocysts by Ziehl-Neelsen and immunofluorescence techniques, the animals were sacrificed; their small intestines were processed and examined for the detection of pathological lesions after histopathological study. In addition, the activity of myeloperoxidase (MPO) was measured in sections of the jejunum. Concerned the results, we observed a statistically significant (P<0.001) increase in the number of oocysts of Cryptosporidium in the stool for sub infected immunosuppressed groups and an increase of MPO activity compared to the corresponding subgroups immunocompetent subgroups. The URMeOH could remove Cryptosporidium oocysts from feces and intestinal sections subgroup infected immunocompetent rats receiving URMeOH. Moreover, the oocysts were significantly reduced in all other subgroups experimental infected compared to infected control subgroups. Intestinal sections in all subgroups received URMeOH revealed a more or less normal architecture. In addition, the reduction of MPO activity level was also detected in all experimental subgroups.